(untitled) (Al-Qamar, 2021)
This research paper is about the concept of morals and literature, and their mutual relevance and their consequences into the society. lts aim is to raise the problem represented in the overlap and intersection between their sub-concepts. The research methodology used was descriptive, theoretical and applied. This study was divided into three sections. The first section dealt with the concept of morals and literature, the second section revolved around their mutual relevance and the third section surrounded the moral paradigms related to the literature. This article simplified the understanding of the concept of morals and literature. It also played a key role in relating morals to the literature.